1995
DOI: 10.21273/jashs.120.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Ester-based Coatings Formulated with Food-compatible Antioxidants in the Prevention of Superficial Scald in Stored Apples

Abstract: Treatments were applied in Italy, United Kingdom, and Spain to test their effectiveness in controlling superficial scald in apples (Malus domestica Borkh.) after cold storage. In Italy where mature `Red Chief' and `Golden Delicious' were stored at 3-4C for 4 months, scald incidence was reduced by postharvest dipping in a sucrose-ester based coating, Semperfresh, formulated with the antioxidants, ascorbyl palmitate, and n-propyl gallate. In the United Kingdom and Spain, early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Ascorbic acid alone reduced scald incidence and severity when apples were stored in CA for 43 weeks, but the effects were not consistent when apples were stored in air (Chellew and Little, 1995). Vegetable oils reduced superficial scald, probably because of a physical effect, and this was not related to chain length of fatty acids or degree of unsaturation (Bauchot et al, 1995a(Bauchot et al, , 1995bChellew and Little, 1995;Dodd and Bester, 1993;Little and Barrand, 1989;Scott et al, 1995b;Smith and Stow, 1994).…”
Section: Food-compatible Antioxidant Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid alone reduced scald incidence and severity when apples were stored in CA for 43 weeks, but the effects were not consistent when apples were stored in air (Chellew and Little, 1995). Vegetable oils reduced superficial scald, probably because of a physical effect, and this was not related to chain length of fatty acids or degree of unsaturation (Bauchot et al, 1995a(Bauchot et al, , 1995bChellew and Little, 1995;Dodd and Bester, 1993;Little and Barrand, 1989;Scott et al, 1995b;Smith and Stow, 1994).…”
Section: Food-compatible Antioxidant Coatingsmentioning
confidence: 99%
“…A sucrose-fatty acid ester coating can improve the storage quality of apples (Smith and Stow, 1994), and, when used with food-compatible antioxidants, can reduce apple scald for a few months (Bauchot et al, 1995b;Little and Barrand, 1989). Bauchot et al (1995b) concluded that the limited control of scald by ascorbyl palmitate plus a sucrose-fatty acid ester is partially related to modification of the internal atmosphere of the apple, and Dodd and Bester (1993) found that the use of ascorbyl palmitate mixed with oil markedly reduced scald . Ascorbic acid alone reduced scald incidence and severity when apples were stored in CA for 43 weeks, but the effects were not consistent when apples were stored in air (Chellew and Little, 1995).…”
Section: Food-compatible Antioxidant Coatingsmentioning
confidence: 99%
“…Elsewhere we report in detail on the effectiveness of the treatments used (Bauchot et al, 1995). In the present paper we describe the changes in the levels of carbon dioxide, oxygen, and ethylene that are associated that have undergone a variety of treatments designed to combat scald.…”
Section: Introductionmentioning
confidence: 99%
“…Com o uso de ésteres de sacarose é possível aumentar o tempo de prateleira de muitos vegetais. Produtos à base de sucroésteres, como o Semperfresh ® , proporcionam uma redução na oxidação de α-farneseno em células hipodérmicas de maçã e pêra 26 , diminuindo assim o escurecimento destas frutas. No Brasil, já foram realizadas pesquisas, com resultados positivos na utilização de sucroésteres no amadurecimento de bananas 27 , tomates 28 e pêssegos 29 .…”
Section: éSteres De Sacaroseunclassified